Acute Hyperglycemia Due to Topical Corticosteroid Administration - Laura Y. Sue; Anna Milanesi (Case Reports in Endocrinology)
We present the case of a 71-year-old man with longstanding, previously well-controlled type 1 diabetes who developed acute hyperglycemia. His insulin requirements, via his insulin pump, increased to nearly five times his typical daily dose. The patient was admitted for evaluation and treatment and started on an insulin infusion. He had minimal insulin requirements with the insulin infusion. History revealed recent use of a super potent topical corticosteroid for a psoriasis flare. The patient was transitioned back to his insulin pump, using his prior to admission settings. He was advised to discontinue using his topical corticosteroid. He had no further hyperglycemic episodes. The clinical presentation is suggestive of corticosteroid-induced hyperglycemia, suggesting that clinically significant changes can occur even with short duration use, particularly with high potency steroids used. This is to our knowledge the first case reported in which the patient required a very significant amount of extra insulin (nearly five times his typical total daily dose) after using high potency topical steroid cream. This case highlights the potentially detrimental effect of topical corticosteroid use in patients with diabetes.